CCRL2, a fringe member of the atypical chemoattractant receptor family. Issue 6 (10th May 2013) - Del Prete, Annalisa; Bonecchi, Raffaella; Vecchi, Annunciata; Mantovani, Alberto; Sozzani, Silvano
<x xml:space="preserve">Abstract</x> The term atypical chemoattractant receptors is generally used to refer to a subset of G‐protein‐coupled receptors devoid of chemotactic activity and characterized by the ability to scavenge chemotactic factors from the inflammatory milieu. However, emerging evidence suggests that this class of receptors is heterogeneous in function. In this Viewpoint, we discuss the properties of CCRL2, a molecule devoid of ligand scavenging functions and suggested to regulate leukocyte recruitment by alternative mechanisms.